UAV applications in wheat crop: a bibliometric approach to the literature - dos Santos Felipetto, Henrique; Mercante, Erivelto; Henrique Viana, Octavio; Carvalho Granemann, Daniel; Robson Elias, Adão (Revista Ciência Agronômica, 2023)
The main objective of this study was to carry out a bibliometric search in the literature on the use of UAVs in the wheat crop. For this purpose, a search of all scientific articles published until 2021 was carried out in the Web of Science database. Subsequently, bibliometric literature analysis techniques were applied using the software VOSviewer, which allowed evaluating the co-authorships between countries and institutions and the co-occurrences of words between studies. The journals and authors that publish the most on this topic were verified. The results indicate a growing trend of publications on UAV applications in the last 7 years, with China, the United States, and the United Kingdom being the main researchers on this topic. However, China stands out with approximately 40% of the publications. This analysis reveals the main current issues and the most influential institutions around the world that have carried out relevant research in scientific publications, showing the journals that include more publications and the collaborative patterns related to the use of UAVs in the wheat crop. Multi-rotor platforms with embedded multispectral cameras are the most used for this purpose. About 27.8% of the publications are from the topic related to the monitoring of productivity/phenotyping. Therefore, this application is in evidence, but further studies on the use of drones in regions with high wheat production, such as South American countries, are needed.